Analytical study to evaluate the relation between vaginal Birth Order and pelvic organ prolapse quantification stages - Kushwaha, Prachi; Soni, Sona (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pelvic organ Prolapse (POP) is the downward displacement of central pelvic organs that are normally located at the level of or adjacent to the vaginal vault. These conditions are common and affect a progressively larger percentage of women as age advances especially in the postmenopausal years. Methods: Data were collected as a retrospective study. Thorough history was taken and physical examination was done. Demographic details of each patient were recorded including age, residence type, education and socio- economic status. A detailed history of all the patients was obtained included parity, live birth and nutrition status. Results: Most of the patients belong to birth order 4 or more than that [73 (62.9%)] followed by birth order 3 [26 (22.4%)] and 2 [16 (13.8%)] whereas 38 (32.7%) patients had birth order >4. In patients with birth order ≥4 and 3 had higher distribution of POPQ stage III and IV respectively. Conclusions: From Present study it can be concluded that vaginal childbirth plays a major role in development of POP. POPQ stages were statistically significant with high birth order.